(untitled) (Revista Cocar, 2019)
Children’s education of the countryside: teaching strategies in multi-serialized classes Resumo Este trabalho discute a Educação Infantil multisseriada do Campo, realidade presente em muitos municípios pelo Brasil. Tem como objetivo relatar um estudo sobre a Educação Infantil do Campo em classes multisseriadas, realizado no município de Baraúna-RN. Recorremos à pesquisa bibliográfica e empírica; utilizamos como instrumento para coleta de dados a entrevista semiestruturada. As professoras em suas estratégias de ensino usam objetos que fazem parte do cotidiano das crianças, para que os/as alunos/as construam uma visão reflexiva sobre a realidade. Nem sempre as estratégias se adequam a todos os níveis de desenvolvimento dos/as alunos/as, mas quando isso ocorre, elas fazem adaptações para tentar atender a todas as crianças. Palavras-chave: Educação Infantil no Campo. Classes Multisseriadas. Estratégias de Ensino. Abstract This paper discusses the Multi-serial Childhood Education of the countryside, a reality present in many cities throughout Brazil. It has as objective: to investigate about the Child Education of the countryside in multi-serialized classes, in the city of Baraúna-RN. We resorted to bibliographical and empirical research; we used the semistructured interview as an instrument for data collection. Teachers in their teaching strategies use objects that are part of children’s daily life, so that students construct a reflective vision about reality. Strategies do not always fit all levels of students development, but when this occurs, they make adaptations to try to meet all children. Keywords: Childhood Education of the countryside. Multi-serialized classes. Teaching Strategies.